A scoping review of current practices on community engagement in rural East Africa: Recommendations for snakebite envenoming. (September 2021) - Moos, Bethany; Williams, David; Bolon, Isabelle; Mupfasoni, Denise; Abela-Ridder, Bernadette; Ruiz de Castaneda, Rafael
Abstract: Community empowerment and engagement is one of the four strategic aims highlighted in the WHO strategy to prevent and control snakebite envenoming. Inappropriate health-seeking behaviours contribute to adverse outcomes, and community engagement is key in driving behavioural change. WHO has highlighted East Africa as a geographical area of concern for snakebite envenoming. The overall aim of the project is to develop a community engagement toolkit for snakebite envenoming and other NTDs. The objective of this scoping review was to identify current practices in recent community engagement in rural East Africa; the applicability of these results to snakebite envenoming are discussed. PubMed, Web of Science, PsycINFO and Google Scholar were searched from 1 January 2017 to 3 September 2020. Search terms were used to identify publications which related to rural communities and health or disease, for both humans and animals. After reviewing the full papers for all geographical areas, 112 publications were included, 30 of which were conducted in East Africa. Papers included nine different countries and covered a broad range of health topics; notably, water, sanitation and hygiene, nutrition, and maternal and child health. Only one publication considered animal health. The most common form of engagement was in the context of a group meeting, lecture, presentation, discussion or question and answer session (63.3%). A variety of locations within the community were used to engage with people, the most common being an individual's household (23.3%). Communication factors was the key influencer for engagement, both positively and negatively. Key barriers to engagement include local languages and health beliefs, literacy levels, mobile phone ownership and the level of mobile Internet coverage, burden of agricultural work and weather conditions. This study provides an extensive overview of recent public health community engagement in East Africa, which will serve as a useful resource for any group seeking to plan an intervention in remote and rural areas in East Africa. Furthermore, it serves as a guide to help tailor community engagement to snakebite envenoming. Highlights: This review includes 30 publications from nine East African countries; only one considered animal health. The most common method of engaging with communities was in a group setting, followed by household visits. Areas highlighted for cross-sectoral collaboration include water, sanitation and hygiene, nutrition and maternal and child health. Communication was the main factor that influenced engagement, positively or negatively. Other key barriers to engagement include poverty, the climate, burden of agricultural work and traditional health beliefs.